Supersense (Sydney : BBC Enterprises Ltd., 1988)
A stunning series of six programmes which reveal the secrets of animal perception for the first time, allowing viewers to immerse themselves in the lives and habits of animals
v.1. Sixth sense v.2. Seeing sense v.3. Sound sense v.4. Super scents v.5. Times of our lives v.6. Making sense
Keywords: Senses and sensation; Perception in animals